Use of the adult attachment projective picture system in psychodynamic psychotherapy with a severely traumatized patient - George, Carol; Buchheim, Anna (Frontiers in Psychology, 2014)
The following case study is presented to facilitate an understanding of how the attachment information evident from Adult Attachment Projective Picture System (AAP) assessment can be integrated into a psychodynamic perspective in making therapeutic recommendations that integrate an attachment perspective. The Adult Attachment Projective Picture System (AAP) is a valid representational measure of internal representations of attachment based on the analysis of a set of free response picture stimuli designed to systematically activate the attachment system (George and West, 2012). The AAP provides a fruitful diagnostic tool for psychodynamic-oriented clinicians to identify attachment-based deficits and resources for an individual patient in therapy. This paper considers the use of the AAP with a traumatized patient in an inpatient setting and uses a case study to illustrate the components of the AAP that are particularly relevant to a psychodynamic conceptualization. The paper discusses also attachment-based recommendations for intervention.